Islam and the state in Myanmar Muslim-Buddhist relations and the politics of belonging - Crouch, Melissa (Oxford University Press, 2016)
This volume explores relations between Islam and Buddhism and the state in Myanmar, offering an informed response to contemporary issues facing the Muslim communities there.